HIPK2 is a new drug target for anti-fibrosis therapy in kidney disease - Nugent, Melinda M.; Lee, Kyung; He, John Cijiang (Frontiers in Physiology, 2015)
In vitro and animal studies continue to elucidate the mechanisms of fibrosis and have led to advancements in treatment for idiopathic pulmonary fibrosis and cirrhosis, but the search for treatments for renal fibrosis has been more disappointing. Here, we will discuss homeodomain-interacting-protein kinase 2 (HIPK2), a novel regulator of fibrosis that acts upstream of major fibrosis signaling pathways. Its key role in renal fibrosis has been validated in vitro and in several murine models of chronic kidney diseases (CKD).